Peran Komunikasi Interpersonal Orang Tua Dalam Menumbuhkan Perilaku Positif Pada Anak Tunarungu - Debvi Nur Aprianti; Hairunnisa Hairunnisa; Annisa Wahyuni Arsyad (Journal of Communication Studies, 2022)
Interpersonal communication between parents and deaf children is needed in fostering positive behavior in children. The quality of the relationship that parents give to their children can determine the moral quality and personality of the child. This study aims to determine, describe how the interpersonal communication of parents who have deaf children can form positive behavior. The type of research used by the researcher is descriptive qualitative, the data source uses non-probability sampling with the sampling technique used is snowball sampling. The results of this study indicate that the 3 key-informants have different ways of teaching deaf children, but still produce positive behavior, deaf children become independent, openness between parents and children, self-confidence of deaf children in interacting with other individuals. built by parents produce positive behavior for children who are deaf. Not being able to use sign language is not one of the obstacles in teaching deaf children to communicate, with body movements and facial expressions as non-verbal language can still make children understand and balanced with verbal language such as using oral in communicating makes children can adapt to the community environment, and have positive behavior.